Pengaruh Model Pembelajaran Think Pair Share Terhadap Hasil Belajar Siswa pada Pembelajaran PKn - Anggraini, Octavica; F, Farida; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of student learning outcomes on Citizenship Education (PKn) subjects using the Think Pair Share (TPS) model. This type of research is a quasi-experimental study with a non equivalent control group design. The sample in the study was Class VA and VB of SDN 18 Pudung. Data collection techniques use tests and observation sheets. Hypothesis testing in this study using the t-test formula. Based on the calculation of the t test (t-test) on the posttest results, the results of tcount = 6.34 and ttable = 1.66 at the significant level α = 0.05 of 1.66, then tcount> ttable. This means there is a significant effect on student learning outcomes using the TPS model.Keywords: Think Pair Share (TPS), PKn, learning outcomes Abstract